Hydroxynaphthalenecarboxamides and substituted piperazinylpropandiols, two new series of BRAF inhibitors. A theoretical and experimental study - Campos, Ludmila E; Garibotto, Francisco; Angelina, Emilio; Kos, Jiri; Gonec, Tomas; Marvanova, Pavlina; Vettorazzi, Marcela; Oravec, Michal; Jendrzejewska, Izabela; Jampilek, Josef; Alvarez, Sergio E; Enriz, Ricardo D (Bioorganic chemistry, 2020)
The oncogenic mutated kinase BRAFV600E is an attractive molecular target because it is expressed in several human cancers, including melanoma. To present, only three BRAF small inhibitors are approved by the FDA for the treatment of patients with metastatic melanoma: Vemurafenib, Dabrafenib and Encorafenib. Although many protocol treatments have been probed in clinical trials, BRAF inhibition has a limited effectiveness because patients invariably develop resistance and secondary toxic effects associated with the therapy. These limitations highlight the importance of designing new and better inhibitors with different structures that could establish different interactions in the active site of the enzyme and therefore decrease resistance progress. Considering the data from our previous report, here we studied two series of derivatives of structural scaffolds as potential BRAF inhibitors: hydroxynaphthalenecarboxamides and substituted piperazinylpropandiols. Our results indicate that structural analogues of substituted piperazinylpropandiols do not show significantly better activities to that previously reported. In contrast, the hydroxynaphthalenecarboxamides derivatives significantly inhibited cell viability and ERK phosphorylation, a measure of BRAF activity, in Lu1205 BRAFV600E melanoma cells. In order to better understand these experimental results, we carried out a molecular modeling study using different combined techniques: docking, MD simulations and quantum theory of atoms in molecules (QTAIM) calculations. Thus, by using this approach we determined that the molecular interactions that stabilize the different molecular complexes are closely related to Vemurafenib, a well-documented BRAF inhibitor. Furthermore, we found that bi-substituted compounds may interact more strongly respect to the mono-substituted analogues, by establishing additional interactions with the DFG-loop at the BRAF-active site. On the bases of these results we synthesized and tested a new series of hydroxynaphthalenecarboxamides bi-substituted. Remarkably, all these compounds displayed significant inhibitory effects on the bioassays performed. Thus, the structural information reported here is important for the design of new BRAFV600E inhibitors possessing this type of structural scaffold.
Keywords: Melanoma; Models, Molecular; melanom; Cell viability; Humans; Phosphorylation; BRAF inhibitors; protinádorové látky; molekulární modely; Molecular modeling; Antineoplastic Agents; ERK phosphorylation; protoonkogenní proteiny B-Raf; Proto-Oncogene Proteins B-raf; fosforylace; lidé